Determining of problem solving strategies used by primary 8, grade students' in mathematics class - Taspinar, Zehra; Bulut, Mehmet (ELSEVIER SCIENCE BV, 2012)
The purpose of this research is to investigate the effect using a combination of different levels of problem solving strategies on primary 8. grade students in math class applied to the teaching of problem solving strategies. For this purpose, 22 eight grade students were taught problem solving strategies throughout 4 weeks (15 hours). In this process, problem solving strategies were introduced to students and were solved the problems that can be solved by different solutions. The strategies that taught in this study are Working Backwards, Finding a Pattern, Adopting a Different Point of View, Making a Drawing, Guess and Check, Accounting for All Possibilities and Organizing Data. Initial and the final of the application, the research problems developed by the researcher were given to students as pre and posttest. Acccording to results, students' problem solving strategies used by the pre-test was very limited, this situation improved in the final test, students were able to use different solutions.
Keywords: problem solving strategies; mathematics education; primary education; teaching methods; Education & Educational Research